IDENTIFICATION OF BAMBOO TYPES (Bambusoideae) IN PONTIANAK CITY - Sisillia, Lolyta; Destiana, Destiana; Reza, Aswan; Lesi Kajamid, Elisia; Tedi Perdana, Fransisko; Rosula Rinto, Stepanus (Jurnal Belantara, 2025)
Pontianak City is one of the major cities in West Kalimantan and has high biodiversity, one is the bamboo plant which has important ecological and economic values. This study aims to identify bamboo and determine the distribution of bamboo in the East Pontianak sub-district. The methods used in this study include field surveys and sample collection in various locations in Pontianak City, as well as morphological and taxonomic identification in the laboratory Results Distribution and Identification of Bamboo Species (Bambusoideae) In East Pontianak District there are three bamboo genera namely Schizostachyum, Bambusa and Thyrsostachys with five types of bamboo with a total of 137 growing points or clumps, including, Schizostachyum brachycladum var "yellow" 6 clumps, Bambusa vulgaris var. Vulgaris 23 clumps, Bambusa vulgaris var. sriata 15 clumps, Thyrsostachys siamensis Gamble 72 clumps, and Bambusa multiplex 21 clumps. The types of bamboo that grow in the East Pontianak area grow at an altitude of 1.35 - 2.1m above sea level with an air humidity of 83 - 91%, soil pH of 4.9 - 6.2%, and temperature of 28 - 32°C.